Flexibility in a Metal–Organic Framework Material Controlled by Weak Dispersion Forces: The Bistability of MIL-53(Al) - Walker, A.; Civalleri, B.; Slater, B.; Mellot-Draznieks, C.; Corà, F.; Zicovich-Wilson, C.M.; Román-Pérez, G.; Soler, J.; Gale, Julian (Wiley-VCH Verlag GMBH, 2010)
Breathtaking MOFs: DFT calculations reveal that the exceptional, thermally induced density change of the metal–organic framework MIL53(Al) is controlled by a competition between short- and long-range interactions and entropic factors. As shown in the picture (C green, Al cyan, O red, H white), dispersive interactions between the phenyl rings are responsible for stabilizing a narrow-pore form at low temperature. At 325–375 K, vibrational entropy causes the structure to expand markedly, permitting large volumes of light gases to be adsorbed.